The tendency of anemia of inflammation in periodontal diseases. Issue 3 (8th February 2023) - Han, Ye; Luo, Zhiqiang; Yue, Zhao Guo; Miao, Li Li; Xv, Min; Chang, Shu; Zhan, Yalin; Hou, Jianxia
Abstract: Anemia of inflammation (AI) is associated with inflammatory diseases, and inflammation-induced iron metabolism disorder is the major pathogenic factor. Earlier studies have reported a tendency of AI in periodontitis patients, but the explicit relationship and possible pathological mechanisms remain unclear. Here, the analyses of both periodontitis patients and a mouse model of ligature-induced experimental periodontitis showed that periodontitis was associated with lower levels of hemoglobin and hematocrit with evidence of systemic inflammation (increased white blood cell levels) and evidence of iron restriction (low serum iron along with a high serum hepcidin and ferritin levels), in accordance with the current diagnosis criteria for AI. Moreover, periodontal therapy improved the anemia status and iron metabolism disorders. Furthermore, the increased level of hepcidin and significant correlation between hepcidin and key indicators of iron metabolism emphasized the pivotal role of hepcidin in the pathogenesis of periodontitis-related AI. Administration of the signal transducer and activator of transcription 3 (STAT3) inhibitors Stattic suggested that the IL-6–STAT3–hepcidin signaling pathway participated in this regulatory process. Together, these findings demonstrated that periodontitis should be considered an inflammatory disease that contributes to the development of AI; furthermore, IL-6–STAT3–hepcidin signaling pathway plays a key regulatory role in the pathogenesis of periodontitis-related AI. Our study will provide new insights into the systemic effects of periodontitis, while meaningfully expanding the spectrum of inflammatory diseases that contribute to AI.